Repercussões do hipotireoidismo gestacional e perinatal experimental na função auditiva da prole de ratas - Oliveira, Priscila Feliciano de (2018)
Introduction: Thyroid hormones (TH) during gestation are critical for fetal growth and development of hearing organ. The lack of maternal TH leads an inadequate development of Organ of Corti with malformation of internal sulcus, tectorial membrane, cochlear ductus and a hair cells differentiation. It can adversely affect the auditory system, which can cause a hearing loss. Experimental studies are performed with postnatal period hypothyroidism induction, but there are no investigations that induce at gestational period. The impact of thyroid hypofunction restricted to the embryonic period remains unknown, which makes this study unpublished. Objective: To evaluate the effect of gestational hypothyroidism on auditory function of adult offspring in rats. Methods: The research was composed by Wistar rats and it was approved by the Ethics Committee on Animal Research of Federal University of Sergipe (Protocol #21/15). Pregnant Wistar rats were given the antithyroid drug methimazole (0.02% - 1-methylimidazole-2-thiol – MMI, in drinking water, ad libitum) from gestational day (GD) 9 to delivery day (GD 21-22), and comprises a offspring from gestational MMI-treated dams group (OGMTD). To lactation hypothyroidism group [offspring from perinatal MMI-treated dams group (OPMTD)] the drug was given from 9ºGD to the 15th postnatal day (PND). Part of the OGMTD and OPMTD groups received replacement of HT with levothyroxine at the concentration of 50 μg / 100 mL in drinking water. All animals were evaluated by tympanometry, distortion product otoacoustic emission (DPOAE) and auditory evoked brainstem response (ABR) at 30, 60, 90 and 120 PND. Results: Our data demonstrated no middle ear dysfunction; regardless of hypothyroidism groups, compliance was lower than the control group (p<0,005). DPOAE was lower in OGMTD from 4 up to 12 kilohertz (kHz) and absent in OPMTD (p<0,001). On the other hand, ABR revealed normal integrity of neural auditory pathways up to brainstem level in the central nervous system, with no latency modification. Additionally, hypothyroidism groups presented a higher electrophysiological threshold (i.e., hearing loss), worse repercussion in OPMTD (p<0,001). Groups treated with levothyroxine did not reveal difference on hearing behavior compared to hypothyroidism groups. Our data suggest that gestational hypothyroidism leads to a cochlear damage function in offspring, with normality of the auditory pathways to the brainsten with moderate to profound sensorineural hearing loss.